AN ATTEMPT TO UNDERSTAND THE RESISTENCE OF CORRUPTION BY ANALYSING DIFFERENT EQUILIBRIA IN ARGENTINA AND CHILE - ACUS, ALGIRDAS (Politologija, 2012)
The study seeks to understand why corruption is so resistant despite a convincing progress in adopting good governance institutions worldwide. It presents one of the very few success stories and aims to evaluate the possibilities to reduce corruption. The study contributes to the theoretical discussion by suggesting a heuristic tool – the stag hunt game – in which game theory and historical institutionalism are combined. This model is applied to the process of modernization analysis in Argentina and Chile. The critical junctures that shifted these countries towards different roads are highlighted. Argentina has remained in the stalemate of corruption, while Chile has managed to establish good governance.